PEKANBARU GOVERNMENT COMMUNICATIONS IN OVERCOMING THE SPREAD OF CORONA VIRUS DISEASE 2019 (COVID-19) - Apriani, Lilis; Handoko, Tito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
At present, Covid-19 in Indonesia is becoming an important discussion and must be addressed immediately because its spread has increased significantly. The communication that must be carried out by the Pekanbaru City Government to the community must always be paid attention to, because this concerns the lives and actions of the Pekanbaru City Government that exist today. The aim of the research is to provide direct communication to the public regarding the handling of Covid-19 which is spreading in the Pekanbaru City Government and how to deal with the spread of Corona Virus Disease 2019 (COVID-19). This study uses the theory of Muhammad (2005) which indicates that communication includes 5 elements, namely: communicator, message, media, communicant, and effect. The research method used is a qualitative research method with data collection techniques of interviews, observation and documentation. The results showed that the communication carried out by the government in tackling the spread of Covid-19 was quite good, in terms of communicators, messages, media, communicants, and effects. Communication was carried out by the City Government through the delivery of information by the Pekanbaru City Communication, Information, Statistics and Coding Service. Factors that impede the communication of the Pekanbaru city government in dealing with the spread of Covid-19 are the spread of hoax information whose level of truth is still in doubt, as well as the distribution of social assistance from the Provincial Government which is problematic due to the implementation of technical guidelines by the local government that are not appropriate. So that the distribution of aid to people affected by Covid-19 is not on target. Keywords: Communication, Government, Covid-19